2018
DOI: 10.1515/jbcpp-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hematological alterations after therapeutic use of dipyrone in healthy adults: a prospective study

Abstract: Background Dipyrone is a non-narcotic analgesic/antipyretic widely used in some countries but prohibited in others due to suspected risk of agranulocytosis. The primary goal of this study was to evaluate hematological alterations in healthy adult volunteers after treatment with dipyrone. Methods The study enrolled 30 healthy volunteers of both genders, aged 19-37 years. They received tablets containing 500 mg of dipyrone sodium to be used four times daily for 7 consecutive days. Before the first administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…S1 in the supplemental material). Metamizole and its structural analogs were removed from the U.S. market in the 1970s due to an increased risk of blood dyscrasias (13,14). Furthermore, the aniline functional group present in linezolid and its metabolites is an important structural alert in medicinal chemistry for myelosuppression risk (see Fig.…”
mentioning
confidence: 99%
“…S1 in the supplemental material). Metamizole and its structural analogs were removed from the U.S. market in the 1970s due to an increased risk of blood dyscrasias (13,14). Furthermore, the aniline functional group present in linezolid and its metabolites is an important structural alert in medicinal chemistry for myelosuppression risk (see Fig.…”
mentioning
confidence: 99%
“…Landwehr et al compared analgesic potency of intravenous paracetamol and intravenous metamizole both in a dose of 1 g and proved their similar efficacy for postoperative analgesia after retinal surgery compared to the control group [56]. Interestingly, metamizole was proven to also act via substance P and the cannabinoid system [57,58] with the involvement of a possible higher reduction in IROA compared to that observed in our previous study [59] and IROA-related postoperative adverse events compared to that in our additional report [60]. In this study, we used 2.5 g of metamizole as PA and observed the incidence of IPPP in 18% of our patients in the metamizole group, whereas in our previous study, we used 1 g of metamizole and observed IPPP in 22.9% of patients [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of metamizole has not been fully elucidated, its effect is mainly related to the inhibition of cyclooxygenases. Although classifi ed as a non-steroidal anti-infl ammatory drug, metamizole has weak anti-infl ammatory properties (2). Despite a well-known good gastrointestinal safety profi le, the reports of spontaneous adverse drug reactions indicate the presence of metamizole-induced blood dyscrasias, including metamizole-induced neutropenia and agranulocytosis, a more severe form (1).…”
Section: Introductionmentioning
confidence: 99%